ANALYSIS OF THE PROCESSES RELATED TO GLOBALIZATION OF ENTERPRISES IN BULGARIA - Yocheva, Gergana (Annals of Spiru Haret University. Economic Series, 2024)
People have been interacting with each other for a long period, through their businesses. Enterprises are the structure of the social economy. Due to the successive economic and social crises in Bulgaria, many companies are on the verge of survival. Through them, society’s expectations for the employment of the population are characterised, which is the main objective of every enterprise. The main objective of this paper is to characterize and analyse the process of increasing economic, social, technical and political interconnections between individuals, countries and organizations.The current context impose a need to develop a system of indicators for the analysis and assessment of the globalization processes that is affecting the whole economy of the country. There is also a need for targeted management actions and the development and implementation of effective strategies that are appropriate to the dynamic changes in the competitive environment.